ARTIFICIAL INTELLIGENCE TOOLS EFFECTIVELY DEVELOPING SELF-DIRECTED LEARNING, INCREASING STUDENTS’ AUTONOMY AND MOTIVATION IN UZBEKISTAN - Shikina, Anastasiya (UC Journal: ELT, Linguistics and Literature Journal, 2025)
This article aims to explore the ability of AI tools to enhance SDL skills and identify the associated changes in learners’ sovereignty and enthusiasm in learners in Uzbekistan. However, much research has been conducted on the use of AI in education at a global level, but few studies have looked at the intervention efficacy of AI in the Uzbek education system. Using an online questionnaire with a quantitative method, the survey samples were sent to 27 undergraduate and graduate students to capture their experiences of AI tools. Quantitative data analysis was employed, with the results showing an influence of the designed AI, reporting greater levels of self-directed learning practices and self-regulation among engaged student groups. The results imply that AI applications can contribute to the development of the educational process in Uzbekistan and other countries, promoting the transition to a more learner-centered learning environment. Hence, this research provides useful information to educators and policymakers interested in the right way to adopt technology in education processes.